Water column circulation drives microplastic distribution in the Martínez-Baker channels; A large fjord ecosystem in Chilean Patagonia. (November 2020) - Castillo, Cristóbal; Fernández, Camila; Gutiérrez, Marcelo H.; Aranda, Mario; Urbina, Mauricio A.; Yáñez, Jorge; Álvarez, Ángela; Pantoja-Gutiérrez, Silvio
Abstract: We investigated the distribution of microplastics in the water column along a large remote estuarine system located between the Northern and Southern Patagonian Ice Fields in Chilean Patagonia, and connected with the Pacific Ocean through the Gulf of Penas. Microplastic particles were found in all samples, with abundances ranging from 0.1 to 7 particles/m 3 . Polymers identified were principally acrylics, PET, and cellophane. The average abundance of microplastics in surface waters was similar along the whole estuary (0.4 ± 0.3 particles/m 3 ) with acrylics and epoxy resins being more abundant near Caleta Tortel, the only small village in the area. The observed higher abundance of microplastics in the deeper waters towards the Gulf of Penas points to intrusions of subsurface waters transporting plastic particles from the ocean into the channel system. This underlines the potential of ocean currents in transporting plastic pollution into pristine fjords and channels in Chilean Patagonia. Highlights: Microplastics occurred in all water samples along the Martínez-Baker Channels. The highest abundances were found in deeper waters toward the ocean. Over 50% of identified microplastics were acrylics, PET and cellophane. An oceanic input of microplastics into this channel system is proposed.